2014
DOI: 10.1002/cctc.201300905
|View full text |Cite
|
Sign up to set email alerts
|

Titania‐Photocatalyzed Transfer Hydrogenation Reactions with Methanol as a Hydrogen Source: Enhanced Catalytic Performance by Pd–Pt Alloy at Ambient Temperature

Abstract: Hydrogenation reactions are of great importance in scientific research and in industry productions. Herein, we designed a novel system to realize photocatalytic transfer hydrogenation by using solar light as the energy input and methanol as the hydrogen source. In this reaction, titania loaded with Pd–Pt bimetallic alloy nanocrystals as a cocatalyst exhibited photocatalytic performance that was remarkably superior to that exhibited by titania with Pd or Pt alone as the cocatalyst. This work has shed light on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Moreover, this TiO 2 −Pd−Pt composite exhibited remarkably superior photocatalytic performances as compared to Pd or Pt alone loaded on TiO 2 . 697 The proposed mechanism is shown in Figure 6. This transformation was shown to be triggered by the existence of Pd−Pt with photoinduced electrons, these electrons being generated by irradiation and transfer from TiO 2 crystals to the Pd−Pt alloy.…”
Section: Carbon Material-immobilized Catalystsmentioning
confidence: 99%
“…Moreover, this TiO 2 −Pd−Pt composite exhibited remarkably superior photocatalytic performances as compared to Pd or Pt alone loaded on TiO 2 . 697 The proposed mechanism is shown in Figure 6. This transformation was shown to be triggered by the existence of Pd−Pt with photoinduced electrons, these electrons being generated by irradiation and transfer from TiO 2 crystals to the Pd−Pt alloy.…”
Section: Carbon Material-immobilized Catalystsmentioning
confidence: 99%
“…Previous investigations have shown that bimetallic catalysts comprising Fe-Ni nanomixtures [14], Pd-Pt cocatalysts [15], Au@Pt core-shell nanocomposites [16] and Au-Ni co-catalysts [17] are examples of synergetic effect in photocatalytic hydrogen production. Particularly, in the photocatalytic system Au-NiO/TiO 2 , it has been found that the addition of NiO increases hydrogen production compared to the monometallic Au/TiO 2 , which was explained in terms of enhancement of the electron (charge) transfer from TiO 2 to the Au-NiO system and the effect of surface plasmon resonance of gold NPs [17].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we are aware, there appear to be only two examples of room temperature TH reactions with methanol. In one example, the TH is driven by light, while in the other the reaction is enabled by an enzyme …”
Section: Methodsmentioning
confidence: 99%